Farsight : futures reviewed. (Copenhagen : Copenhagen Institute for Futures Studies)
FARSIGHT is a quarterly publication that explores possible futures with the aim of provoking and inspiring change in the present. FARSIGHT is published by the Copenhagen Institute for Futures studies, an independent and non-profit think tank (NGO) with half a century’s experience in using futures studies to address the challenges facing societies and organisations. Analyses by our resident futurists are included alongside feature articles and interviews from an international team of freelance journalists and expert contributors so that each issue offers an extensive and multifaceted deep dive into a specific topic of interest to a broad range of readers and decision makers. Our guiding editorial principle is that the future can never be predicted, and that multiple possible futures exist at any given time. Our goal is to unfold the futures ahead in all their kaleidoscopic complexity and to help individuals better understand their own agency in shaping the world that they desire.